Implikasi Islamic Parenting pada Kecerdasan Emosional dan Spiritual Santri Pondok Pesantren Tahfidzul Qur’an lil Athfal Nurul Islam Cerme Gresik - Syamsi, Moh; Khamim, Nur; Izzah, Azimatul (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
This research is motivated by the interest in Islamic Parenting activities as an effort to Build Children's Emotional and Spiritual Intelligence, and to analyze it within the Nurul Islam Islamic Boarding School institution, which can foster children's emotional and spiritual intelligence. The method used is a qualitative method. Data collection was conducted through interviews and observations. The data used are in the form of intensive observations, interviews, and observations so that a holistic picture is obtained of the form of Islamic Parenting and its implications on the emotional and spiritual intelligence of students of the Tahfidzul Qur'an Islamic Boarding School lil Athfal Nurul Islam Cerme Gresik. The results of this study show that Islamic Parenting activities can form the emotional and spiritual intelligence of children at the Tahfidzul Qur'an lil Athfal Nurul Islam Cerme Islamic Boarding School covering several aspects, including: (1) The categories of the basics of religion and worship in the form of, Asma'ul Husna Reading, Al-Ma'tsurat Reading, Reading of important letters in the Qur'an; (2) Category of children's manners and ethics Saying greetings when meeting teachers, praying when entering and leaving the assembly/Assembly and when ending all activities in the institution/Dismissal Program; (3) Categories of social moral education and love saying; (4) The category of mahmudah morals, namely the Tahfidz program and the Tahfidz Competition); (5) The category of Tarbiyyah and Ta'lim is in the form of religious lectures before the Dzuhur prayer and the Dhuhur prayer.